Concurrency control based on role concept. (15th November 2007) - Enokido, Tomoya
A Role-Based Access Control (RBAC) model is used to make a system secure. In addition to keeping systems secure, objects have to be consistent in the presence of multiple transactions. Traditional locking protocols and timestamp ordering schedulers are based on 'first-comer-winner' and 'timestamp order' principles to make multiple conflicting transactions serialisable, respectively. In this paper, we discuss concurrency control algorithms based on the significance of roles. We discuss a Role Ordering (RO) scheduler so that multiple conflicting transactions are serialisable in a significant dominant relation of roles. We evaluate the RO scheduler as compared with the Two-Phase Locking (2PL) protocol.